Respuesta :
Answer:
16
Step-by-step explanation:
1. 8 -(-12) + (-4)
2. 8+12-4
3. 20-4
4. 16
Answer: - 8 – (2)(-6) + (-4) = - 2
Step-by-step explanation:
You need to follow BIDMAS
1. Brackets
2. Indices
3. Division
4. Multiplication
5. Addition
6. Subtraction
First we multiply the minus with numbers found in the brackets
- 8 - (2)(-6) + (-4)
- (2)
-1 × 2
= -2
-2 (-6)
-2 × -6
= +12
+ (-4)
+1 × -4
= -4
*Remember +×+=+ -×-=+ +×-=- -×+=-
Then you have:
- 8 - 2 + 12 - 4 = -2
*To work this out you first need to group those that are in the minus group and those which are in the plus group:
-8 -2 -4 are in the minus group.
+ 12 is in the plus group.
Forget about the the symbols and only imagine the groups, now the numbers in the group, you need to add them:
Minus group 8+2+4= 14
Plus group 12
Now we subtract the 14 from 12:
14 - 12 = 2
Now the farthest number from 0 gets the symbol, in this case since 14 is the fathest, it is from the minus group so the final number gets a minus;
-2